A life‐of‐mine approach to fauna monitoring is critical for recovering functional ecosystems to restored landscapes. (15th December 2021) - Cross, Sophie L.; Bradley, Holly S.; Tudor, Emily P.; Craig, Michael D.; Tomlinson, Sean; Bamford, Michael J.; Bateman, Philip W.; Cross, Adam T.
Abstract : Mineral extraction activities are intensely disruptive to ecosystems and their associated fauna. Few countries globally have comprehensive legislation surrounding mine site restoration, but within Australia, restoration of discontinued mine sites is a legislative requirement. However, substantial ambiguity regarding the optimal techniques for restoring biodiverse and functional fauna assemblages remains, and monitoring activities typically focus on vegetation communities despite functioning ecosystems being reliant on key trophic interactions involving fauna. When fauna are considered, monitoring efforts typically yield baseline surveys of species richness and the presence or absence of conservation‐significant taxa. Even where complete ecosystem recovery is not the goal of post‐mining ecological recovery, we argue that there is a critical need for a life‐of‐mine approach to fauna monitoring underpinned by greater dialog between researchers, environmental regulators, and the mining industry. Environmental Impact Assessments should include requirements for the consideration of all potential impacts of mining on the structure, behavior, and ecological roles of fauna communities, restoration practices must facilitate the return of functional, resilient, and biodiverse fauna communities to restored post‐mining landscapes, and the scope of monitoring practices should be broadened to a holistic examination of fauna communities. Recognizing, quantifying, and monitoring the impacts of mining activities and subsequent rehabilitation or restoration on fauna is vital to understanding how anthropogenic disturbances affect natural ecosystems, and in assisting in the successful recovery of ecosystem functionality to areas that have been damaged, degraded, or destroyed.